Association of Lp(a) (Lipoprotein[a]) and Hypertension in Primary Prevention of Cardiovascular Disease: The MESA. Issue 2 (13th December 2022) - Rikhi, Rishi; Bhatia, Harpreet S.; Schaich, Christopher L.; Ashburn, Nicklaus; Tsai, Michael Y.; Michos, Erin D.; Chevli, Parag A.; Herrington, David M.; Tsimikas, Sotirios; Shapiro, Michael D.
Abstract : Background: This study explored the longitudinal relationship of Lp(a) (lipoprotein[a]) and hypertension to cardiovascular outcomes in a large multiethnic cohort free of baseline cardiovascular disease. Methods: Individuals from the MESA (Multi-Ethnic Study of Atherosclerosis; N=6674) were grouped as follows: group 1: Lp(a) <50 mg/dL and no hypertension; group 2: Lp(a) ≥50 mg/dL and no hypertension; group 3: Lp(a) <50 mg/dL and hypertension; and group 4: Lp(a) ≥50 mg/dL and hypertension. Kaplan-Meier curves and multivariable Cox proportional hazard models were used to assess the relationship of Lp(a) and hypertension with time to cardiovascular disease events. Results: Mean follow-up time was 13.9 (5.0) years and 809 participants experienced a cardiovascular disease event. A statistically significant interaction was found between Log[Lp(a)] and hypertension status ( P =0.091). Compared with the reference group (Lp[a] <50 mg/dL and no hypertension), those with Lp[a] ≥50 mg/dL and no hypertension had no increased risk for cardiovascular disease events (hazard ratio, 1.09 [95% CI, 0.79–1.50]). However, those with Lp(a) <50 mg/dL and hypertension or Lp(a) ≥50 mg/dL and hypertension demonstrated a statistically significant increase in risk compared to the reference group (hazard ratio, 1.66 [95% CI, 1.39–1.98]) and (hazard ratio, 2.07 [95% CI, 1.63–2.62]), respectively. Among those with hypertension, Lp(a) was associated with a significant increase in cardiovascular disease risk (hazard ratio, 1.24 [95% CI, 1.01–1.53]). Conclusions: Although the major contribution to cardiovascular risk was hypertension, elevated Lp(a) significantly modified the association of hypertension with cardiovascular disease. More research is needed to understand mechanistic links among Lp(a), hypertension, and cardiovascular disease.